Volleyball Achievements Analysis Of POPDA Men's Volleyball at East OKU Regency - Fery Ardianto; Meirizal Usra; Rostika Flora; Iyakrus Iyakrus (Universitas PGRI Palembang, 2021)
The background of this research is due to the volley ball is the sports featured East OKU regency, however lately achievements of volleyball East OKU regency decreased in POPDA. Coaching volleyball is important to do, because it can affect the development of the sport. Sports coaching volleyball cannot be done instantaneously, but rather through a variety of processes and stages in a current period of time. Some of the components of coaching sport achievements, are: (1) Financial Support, (2) the Organization and structure of the policy of unified sports, (3) Foundation and participation, (4) Identification and development of talent, (5) Fostering the achievements of an elite group or system of rewards and support on the after career, (6) sports Infrastructure or training facilities, (7) the Provision of a coach, the coaching and the quality of training, (8). The quality of competition, (9). Scientific research, and (10). Environmental media and sponsorship. The method used in this research is the qualitative and quantitative descriptive. The analysis Model used is the model logic. Model logic can not be described, namely the Planned work consisting of input and activities, as well as the Intended results consisting of the Outputs, outcomes and Impact. By using logic is expected to get optimal results in analyzing the coaching achievements of volleyball POPDA East OKU regency. Techniques in the collection of research data are observations, interviews and questionnaires. The result of the analysis of volleyball achievement coaching POPDA East OKU regency is 57.59 % with enough categories. With input variable details get a percentage of 68.99%, Activities variables get a percentage of 66.77%, Output variables get a percentage of 46.96%, Outcome variables get a percentage of 53.91% and Impact variables get a percentage of 51.30%.